Composição fotojornalística e história: função testemunhal como ato performativo e interação de linguagens - Casadei, Eliza Bachega [UNESP] (My University, 2014)
Assuming that testimony in photojournalism must be understood as a historical and performative act, the aim of this article is to discuss how the testimonial function of journalistic photography was constantly re-signified in Brazilian news magazines during the twentieth century. This redefinition has a relation with the different ways in which testimonial function was hinged to news report (in its broadest elements) and how this imperative appeared on its discursive form in writing narrative. As trustee of a narrative intended to be realistic, photojournalism articulates, from techniques and codes of narration, a series of referential and informational strategies. These strategies, however, have changed over time, based on different modes of narration by image and its accreditation in reality.

A partir do pressuposto de que o caráter de testemunho no fotojornalismo deve ser entendido como uma articulação histórica e como um ato performativo, o objetivo do presente artigo é discutir o modo como a função testemunhal da fotografia jornalística foi constantemente ressignificada nas revistas brasileiras de informação ao longo do século XX. Tal ressignificação tem relação com os diferentes modos em que a própria função testemunhal esteve articulada à reportagem (em seus elementos mais amplos) e a forma como esse imperativo aparecia em sua forma discursiva na narrativa escrita. Como fiduciário de uma narrativa que se pretende realista, o fotojornalismo articula, a partir de técnicas e códigos de narração diversos, uma série de estratégias referenciais e informativas que, contudo, mudaram com o passar do tempo, articulando diferentes modos de narração pela imagem e de credenciamento perante o real.
Photojournalistic composition and history: testimonial function as performative act and languages interactions
Keywords: Photojournalism; Testimonial function; History; Fotojornalismo; Função testemunhal; História